2016
DOI: 10.1155/2016/7652450
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Optimized Ammonia and Ethanol Sensing Using Ce Doped Tin Oxide Thin Films in a Novel Flow Metric Gas Sensing Chamber

Abstract: A simple process of gas sensing is represented here using Ce doped tin oxide nanomaterial based thin film sensor. A novel flow metric gas chamber has been designed and utilized for gas sensing. Doping plays a vital role in enhancing the sensing properties of nanomaterials. Ce doped tin oxide was prepared by hydrothermal method and the same has been used to fabricate a thin film for sensing. The microstructure and morphology of the prepared materials were analysed by SEM, XRD, and FTIR analysis. The SEM images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…FTIR spectroscopy analysis of Ce-doped SnO 2 revealed that the absorption band at 3411.55 cm −1 accorded with the Sn-OH group. An important peak appeared near 667.49 cm −1 is owing to the antisymmetric stretching mode of Sn-O-Sn of the surface bridging oxide created attributable to the condensation of near to the surface vibrations of the -OH group [35]. This peak validates the successful formation of the SnO 2 nanoparticle.…”
Section: Ftirmentioning
confidence: 62%
“…FTIR spectroscopy analysis of Ce-doped SnO 2 revealed that the absorption band at 3411.55 cm −1 accorded with the Sn-OH group. An important peak appeared near 667.49 cm −1 is owing to the antisymmetric stretching mode of Sn-O-Sn of the surface bridging oxide created attributable to the condensation of near to the surface vibrations of the -OH group [35]. This peak validates the successful formation of the SnO 2 nanoparticle.…”
Section: Ftirmentioning
confidence: 62%
“…This facility can save time and installation costs. Such units, being portable, can be connected at any suitable measurement point on a shop floor to measure certain parameters such as water flow, gas flow, 4 displacement, air pressure, and so on.…”
Section: Introductionmentioning
confidence: 99%